Relationship Between Picky Eating Behavior and Level of Nutrient Adequacy in Preschool Children - Aziseh, Nur; Hakiki, Muchammad Insan Kharisma (Media Gizi Indonesia, 2024)
Picky eating behavior or selective eating behavior in children poses a significant difficulty to parents during the preschool years of growth and development. This may have an impact on the range of foods that kids eat. Food variety restrictions will affect how much energy, protein, fat, and carbohydrates are consumed. This study was aimed to analyze the relationship between picky eating behavior and the level of nutrient adequacy in preschool children in Buduran District, Sidoarjo Regency. The method of this study was a cross-sectional study design involving 64 preschool children as respondents who were selected proportionally by random sampling method. Data were collected by completing the Child Eating Behavior Questionnaire (CEBQ) and Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data analysis was performed using the Spearman Rank Correlation test. The study found a significant correlation between picky eating behavior and carbohydrate adequacy (p=0.014). Specifically, 51.6% of the subjects exhibited picky eating behavior, and among them, a significant proportion had a carbohydrate intake classified as deficient. The findings underscore the importance of targeted nutritional interventions for children with picky eating behaviors to ensure balanced nutrient intake.